Understanding stakeholders' perspectives behind wildfires in Sicily: A Q‐methodology approach - Erika Piroli; Donato Salvatore La Mela Veca; Jay Mistry; Yiannis Kountouris (People and Nature)
Abstract Mediterranean wildfires persistently challenge regions due to climatic factors, changing land use, and abandonment of rural areas, posing threats to both ecosystems and human well‐being. Current fire management emphasizes fire exclusion, neglecting traditional methods and socio‐ ecological processes, thereby elevating the risk of catastrophic events and negatively impacting ecosystems. Collaborative efforts among stakeholders and decision makers are essential for effective wildfire mitigation; lack of engagement perpetuates conflicts, underscoring the need to integrate diverse perspectives to enhance environmental management policies. Focusing on Monreale, Sicily, as a representative of fire‐prone Mediterranean landscapes, this study uses Q‐Methodology to investigate stakeholder attitudes toward the causes and drivers of wildfires. Using Q‐Methodology, the research identifies shared values and discrepancies among stakeholders, revealing information on acceptable wildfire policies by discerning areas of consensus. The paper delves into various perspectives on socioeconomic and political dimensions in Sicily, unravelling conflicts and consensus areas for advancing fire management objectives. It concludes with policy insights and recommendations for future research. Read the free Plain Language Summary for this article on the Journal blog.